The Influence of Peer Counsellors’ Activities on Student Discipline in Public Secondary Schools in Kisumu Municipality - Kute , Berther (African Journal of Education,Science and Technology (AJEST), 2015)
Management of student discipline is one of the major challenges to teachers in learning institutions. Incidents of student indiscipline are on the increase in Kenya resulting into among others; property damage, students‘ deaths, arson, increased student drop out, poor performance and rape in some secondary schools. Secondary schools in Kisumu Municipality have had increased cases of student absenteeism, truancy, drug abuse and inacceptable sexual conduct over the years leading to increased school drop outs. This study examines the role that peer counsellors play in enhancing management of student discipline in public secondary schools in Kisumu Municipality. The paper examines how peer counselling activities influence student discipline in public secondary schools. Cross-sectional survey design was used in the study. The study population comprised 28 head teachers, 28 heads of guidance and counselling department, 532 peer counsellors and 3,250 students in 28 public secondary schools. Stratified random sampling was used to select 10 head teachers, 10 Heads of Department of Guidance and Counselling, 110 peer counsellors and 300 form two and three students. Questionnaire and interview guide were used to collect data. Questionnaires were administered to heads of guidance and counselling and students while head teachers were interviewed, face to face. Descriptive statistics in the form of frequencies and percentages were used to analyze the quantitative data generated by questionnaires while qualitative data from interviews were transcribed and organized into themes, categories and subcategories as they emerged during the study. The main findings of the study were that peer counsellors engaged in activities of counselling and referrals, setting of their programme of activities as well as inducting new members. Peer counsellors also encouraged peer support activities in health, drama and music to influence the students‘ behaviour hence improve discipline and were most competent in dealing with issues of absenteeism, truancy and drug abuse. The study recommended that peer counsellors improve on variety of activities carried out in schools and involve more students in those activities.